2008
DOI: 10.1007/s11154-008-9101-5
|View full text |Cite
|
Sign up to set email alerts
|

β-cell failure as a complication of diabetes

Abstract: Type 2 diabetes mellitus is a complex disease characterized by β-cell failure in the setting of insulin resistance. In early stages of the disease, pancreatic β-cells adapt to insulin resistance by increasing mass and function. As nutrient excess persists, hyperglycemia and elevated free fatty acids negatively impact β-cell function. This happens by numerous mechanisms, including the generation of reactive oxygen species, alterations in metabolic pathways, increases in intracellular calcium and the activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
170
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(178 citation statements)
references
References 189 publications
3
170
0
5
Order By: Relevance
“…In vitro studies have shown that β-cell lipotoxicity is directly induced by palmitate, at least in part via pathways primarily involving ER stress and ROS [42][43][44].…”
Section: Islet Inflammation Induces β-Cell Dysfunction In T2dmentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro studies have shown that β-cell lipotoxicity is directly induced by palmitate, at least in part via pathways primarily involving ER stress and ROS [42][43][44].…”
Section: Islet Inflammation Induces β-Cell Dysfunction In T2dmentioning
confidence: 99%
“…Palmitate is the most abundant saturated FFA in blood, and the deleterious effects of palmitate, collectively termed as 'lipotoxicity', on β-cells are well documented [41]. In vitro studies have shown that β-cell lipotoxicity is directly induced by palmitate, at least in part via pathways primarily involving ER stress and ROS [42][43][44].…”
Section: Islet Inflammation Induces β-Cell Dysfunction In T2dmentioning
confidence: 99%
See 1 more Smart Citation
“…4 --6 Chronic hyperglycaemia as observed in type-2 diabetes, or acute hyperglycaemia, as a result of ingestion of a meal causing postprandial glucose and insulin excursions, may increase platelet activation and reactivity. 7,8 Foods such as garlic, cocoa, tomatoes, kiwi fruit, berries and so on have been shown to have anti-platelet properties that may help reduce the risk of thrombosis. 9 --12 We have previously reported 13 a postprandial reduction in platelet aggregation, in healthy men and women, in response to a high carbohydrate, low fat meal (69% energy from carbohydrate, 16% from protein and 15% from fat).…”
Section: Introductionmentioning
confidence: 99%
“…At the beginning of the disease, pancreatic beta cells adapt to insulin resistance by increasing their mass and secretory function. Nevertheless, the sustained hyperglycaemia and hyperlipidaemia eventually exert a negative impact on beta cell function and lead to impaired insulin secretion and decreased insulin gene expression, ultimately causing beta cell apoptosis [1,2]. Moreover, the follow-up of beta cell mass in diabetic patients and in people strongly at risk for diabetes and their response to pharmacological treatment may be crucial for early diagnosis and treatment selection, making the search for beta cell mass markers a high priority for investigation [3].…”
Section: Introductionmentioning
confidence: 99%